TEMPORAL VARIATION OF AEROBIC CAPACITY AND HEART RATE PARAMETERS OF INDIVIDUALS EXPOSED TO THE SAME PROFESSIONAL PERFORMANCE STANDARD (Fiep Bulletin - online, 2017)
The aim of the study was to survey aimed how aerobic capacity and heart rate values in bus drivers aged 25-57 yearsvaried over a time interval of two years. The precarious occupational health, for the bus drivers, is relatively frequent among theseworkers. National and international studies have shown that the bus drivers fall ill in and die a different way compared to thepopulation in general. The work was observational, punctuated for two consecutive years and consisted of observations, in threedistinct moments, of values of aerobic capacity and heart rate. The study sample consisted of 179 males, aged 25-57 years, allbus drivers belonging to a company of interstate transportation from Bahia-Brazil. The subjects were divided in to five age groups.The data collected were introduced into referred computerized program SPSS11.0, to apply statistical treatments. This workemphasizes that through the physical evaluations performed the individuals present, in a general way, an improvement in theirindicators of aerobic capacity (VO2 maximum) and heart rate with the passage of time. We still need to deepen into morescientific studies about major changes in working conditions and workplace, and healthy habits of the bus drivers that arerequired in order to minimize the impact on the occupational health of these workers. Therefore, it is believed that a program ofphysical evaluation and health promotion is essential for better working conditions for these workers.